Un vocabulari pornogràfic francès-català inèdit. - PUIGMALET, JOAN (Scripta, 2014)
Antoni Bulbena Tosell is the author of an unpublished, pornographic vocabulary French- Catalan Catalan-French, a manuscript called the Flora pornogràfica francesa: suplement al argot francès / Flore pornographique catalane: supplément à l'argot catalan. It was written around 1921 and reserved for not being published. Bulbena is the author of a controversial linguistic work, among which are various dictionaries, some of them between Catalan and French. The latest is the Diccionari de les lléngues francesa & catalana / Dictionnaire catalan-français (1921), that includes two appendixes, a «Vocabulari d'argot francès» and a «Vocabulari d'argot catalan». The Flora is thus a pornographic supplement to the lexicon of these vocabularies. Moreover, the title Flora pornogràfica seems to refer to a pornographic French lexicography work that contains obscene words from books by Émile Zola and other naturalist writers: La flore pornographique (1883) by Ambroise Macrobe. Slang sexual terms from the Bulbena's Flora, with a special focus on the theme of prostitution, have linguistic and cultural interest both for the Catalan and the French language